2010
DOI: 10.1100/tsw.2010.65
|View full text |Cite
|
Sign up to set email alerts
|

New Therapeutic Targets for Mood Disorders

Abstract: Existing pharmacological treatments for bipolar disorder (BPD) and major depressive disorder (MDD) are often insufficient for many patients. Here we describe a number of targets/compounds that clinical and preclinical studies suggest could result in putative novel treatments for mood disorders. These include: (1) glycogen synthase kinase-3 (GSK-3) and protein kinase C (PKC), (2) the purinergic system, (3) histone deacetylases (HDACs), (4) the melatonergic system, (5) the tachykinin neuropeptides system, (6) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 125 publications
3
27
0
3
Order By: Relevance
“…An analysis of predicted mRNA targets suggested that miR-34a regulate VEGFA, a growth factor implicated in depression in both humans and animal model (Dwivedi 2011). In addition, an important study revealed that miR-34a (down-regulation) and miR-144 (upregulation) could target the ERK-MAPK signaling pathway that had been known to involve in depressed and bipolar disorder (Zhou et al 2009;Machado-Vieira et al 2010), which paralleled to our present study. Mature miRNAs (miR-200a, miR-200b, and miR-200c) were predominantly associated with soluble components of the synaptic fractions (Lugli et al 2008).…”
Section: Discussionsupporting
confidence: 85%
“…An analysis of predicted mRNA targets suggested that miR-34a regulate VEGFA, a growth factor implicated in depression in both humans and animal model (Dwivedi 2011). In addition, an important study revealed that miR-34a (down-regulation) and miR-144 (upregulation) could target the ERK-MAPK signaling pathway that had been known to involve in depressed and bipolar disorder (Zhou et al 2009;Machado-Vieira et al 2010), which paralleled to our present study. Mature miRNAs (miR-200a, miR-200b, and miR-200c) were predominantly associated with soluble components of the synaptic fractions (Lugli et al 2008).…”
Section: Discussionsupporting
confidence: 85%
“…A causal link between these two was also very recently demonstrated by several authors [50][51][52][53][54]. Moreover, different cell types studied in anxious mice showed a strong accumulation of intracellular ROS, in comparison to non-anxious mice, suggesting that oxidative stress is present in various cortex areas, as well as in hippocampus and cerebellum [55,56].…”
Section: Discussionsupporting
confidence: 58%
“…Signaling pathways targeted by miR-144 include the protein kinase C (PKC), Wnt/β-catenin, and PTEN pathways [45]. Some of them have been shown to be involved in the development of depression [49,50]. In addition, miR-144 was reported to be selectively upregulated in the aging brain of humans and was suggested to have neuroprotective functions.…”
Section: Discussionmentioning
confidence: 99%